Efficacy of Ginkgo biloba extract in amyloid PET-positive patients with mild cognitive impairment - Yang, YoungSoon; Koo, Min-Seong; Kwak, Yong Tae (Frontiers in Neurology, 2025)
BackgroundMild cognitive impairment (MCI) with amyloid PET positivity represents a prodromal stage of Alzheimer’s disease (AD), yet no disease-modifying therapies are currently approved. Ginkgo biloba, traditionally used in East Asian and European ethnomedicine as an oral decoction or standardized extract to support memory and cognitive function, is commonly utilized, however, its efficacy as monotherapy in biomarker-confirmed MCI remains uncertain. Aβ oligomers, produced by abnormal cleavage of amyloid precursor protein, disrupt synaptic function and contribute to cognitive decline.ObjectiveThis study evaluated whether Ginkgo biloba alone, without adjunctive anti-dementia medication, could provide clinical and biomarker benefits in amyloid PET–positive MCI patients. Plasma MDS-Oaβ (Multimer Detection System–Oligomeric Aβ), a dynamic biomarker reflecting Aβ oligomerization tendency, was used to explore mechanistic relevance.MethodsIn this retrospective cohort study, 64 amyloid PET–positive MCI patients were followed for 12 months. Participants received either oral Ginkgo biloba monotherapy (240 mg/day, n = 42) or standard cognitive enhancers (n = 22). Clinical outcomes included the Korean version of the Mini-Mental State Examination (K-MMSE), Clinical Dementia Rating–Sum of Boxes (CDR-SB), Korean Instrumental Activities of Daily Living (K-IADL), and Neuropsychiatric Inventory (NPI). Plasma MDS-Oaβ levels were assessed at baseline and at 12 months.ResultsAt 12 months, the Ginkgo group showed significantly higher responder rates (100% vs. 59.1%, p < 0.001), no conversion to AD dementia (0% vs. 13.6%, p = 0.037), and greater improvement in K-MMSE and K-IADL scores. MDS-Oaβ levels decreased significantly in the Ginkgo group (p < 0.001) but not in the control group. No significant between-group differences were observed in CDR-SB or NPI scores.ConclusionGinkgo biloba monotherapy was associated with preserved cognition, improved daily functioning, and reduced plasma Aβ oligomerization in amyloid PET–positive MCI patients. These findings suggest potential disease-modifying effects and warrant further validation in prospective, biomarker-based clinical trials.